Finite Element Analysis for Acoustic Wave Transmission in Ultrasonic Tomography Application - Pusppanathan, Jaysuman (International Journal of Integrated Engineering, 2017)
A study of acoustic wave transmission through obstacles and boundary surface for ultrasonic tomography applications has been carried out. Ultrasonic tomography for water – crude oil two phase flow sensing relies upon the complex ratio of sound pressure to particle velocity which is the acoustic impedance matching. According to Snell’s Law, the ultrasonic transmission properties can be obtained on the basis of incidence angle, acoustic impedance and basic frequency of ultrasound, material and thickness of the pipeline. These parameters correspond to maximum transmission of an ultrasonic wave from one medium to another when the characteristic impedance is matched. To investigate the wave’s transmission and diffraction on water – crude oil boundaries, several simulations using finite element method (FEM) have been carried out. The simulated result images successfully visualize the ultrasonic wave transmission and reflection characteristic in the two-phase liquid flow tomography system. Thus, the wave propagation behavior in the boundaries is also presented. The information and results obtained is useful for further development for ultrasonic tomography multiphase flow measurement.